The Analysis of Nutritional Status and Physical Fitness Level with Sport Education Outcomes in Students of Samarinda Negeri 011 Elementary School - Ruslan Unmul; Rusli Rusli; Nurjamal Nurjamal; Hendry Ismawan; Hamdiana Hamdiana (Nicolaus Copernicus University in Toruń, 2020)
The study aims to determine the relationship of nutritional status and physical fitness level with the learning outcomes of sports education in students of Samarinda Negeri 011 elementary school. The study is a descriptive research which taking all students of Samarinda Negeri 011 elementary school  as a population. A simple random sampling technique was applied in this study resulted 40 male students selected. A correlation and regression analysis techniques were conducted in this study for data analysis using the SPSS Version 16.00 program at a significant level of 95% or α = 0.05. Results showed three main conclusions in this study that are (1). There is a correlation between nutritional status and learning outcomes in sports education for elementary school students in Negeri 011 Samarinda with an r value of 0.519, that 26 students have a normal nutritional status, 13 are below normal and 1 is overweight. (2). There is a relationship between physical fitness and learning outcomes in sports education for students of SD Negeri 011 Samarinda with a r value of 0.815 which resulted 36 students have less physical fitness while others are medium. (3). There is a relationship between nutritional status and physical fitness together with the learning outcomes of students in Elementary School of  Negeri 011 Samarinda with an R value of 0.833.